Recommendations for blended learning implementation COVID-19 pandemic atmosphere at Indonesian University - Clara Hetty Primasari; Saverius Rischo Setyo Kurniawan; Pamungkas Setyo Wibowo; Yohanes Priadi Wibisono (Universitas 'Aisyiyah Yogyakarta, 2022)
Kampus Merdeka, launched by the Ministry of Education and Culture, calls for increased use of technology in the learning process at the university, followed up by the policies of several universities in Indonesia to implement the Blended Learning method. Several universities in Indonesia started to implement the strategy, but in reality, the implementation was inseparable from the unpreparedness faced by the academic community in its application. The outbreak of COVID-19 further exacerbates this unpreparedness. Thus, this research aims to measure the level of readiness for Blended Learning implementation and provide several recommendations on how people cope with this situation. This research used the ELR (E-Learning Readiness) Model to measure readiness in applying Blended Learning methods. The E-Learning Readiness model used in this study was the Aydin Tasci E-Learning Readiness model. The overall readiness level for Blended Learning implementation is 3.58. This result shows that the level of readiness is at the ready stage and needs a slight increase. This result suggests several recommendations for Blended Learning implementation, especially in this COVID-19 atmosphere.